POVERTY REDUCTION, GOVERNMENT EXPENDITURE AND ECONOMIC GROWTH IN NIGERIA - ORIAKHI , Marian Omosivie (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2021)
This Study examines the relationship between poverty reduction, government expenditure, and economic growth in Nigeria. It aims at proving that there is a bi-directional causal relationship between these variables. A Vector Error Correction Model was specified, and variables included in the model were Poverty Reduction (POVRd), Total Government Expenditure (TGEXP), Real Gross Domestic Product Per Capita (RGDPpc) as a proxy for Economic Growth, and Natural Resource Rents (NRENT). Time series data was analyzed for a period of thirty eight (38) years. The Study employed the Block Exogeneity Wald Test to check for causality between variables, the Vector Error Correction Model (VECM) to analyze the speed of adjustment process and short run transmission mechanism among the variables, the Forecast Error Variance Decomposition to examine total variability in variables due to shocks in itself and in other variables of the model, and the Inverse Roots of AR Characteristics Polynomial to check the state of impulse responses in the estimated model. Findings indicate that there exists a bi-directional relationship between variables. Each variable explained to different percentage levels, variations in shocks in itself and in other variables of the model at different periods. In general, there exists a bi-directional causality between total government expenditure and poverty reduction in Nigeria. The study concludes with recommendations for increase in government expenditure to bring about reduction in poverty, the adoption of pro-growth and pro-poor policies and a transparent and corruption free governance.